16p11.2 deletion syndrome mice perseverate with active coping response to acute stress – rescue by blocking 5‐HT2A receptors. Issue 6 (10th November 2017) - Panzini, Chris M.; Ehlinger, Daniel G.; Alchahin, Adele M.; Guo, Yueping; Commons, Kathryn G.
Abstract: In humans a chromosomal hemideletion of the 16p11.2 region results in variable neurodevelopmental deficits including developmental delay, intellectual disability, and features of autism spectrum disorder (ASD). Serotonin is implicated in ASD but its role remains enigmatic. In this study we sought to determine if and how abnormalities in serotonin neurotransmission could contribute to the behavioral phenotype of the 16p11.2 deletion syndrome in a mouse model (Del mouse). As ASD is frequently associated with altered response to acute stress and stress may exacerbate repetitive behavior in ASD, we studied the Del mouse behavior in the context of an acute stress using the forced swim test, a paradigm well characterized with respect to serotonin. Del mice perseverated with active coping (swimming) in the forced swim test and failed to adopt passive coping strategies with time as did their wild‐type littermates. Analysis of monoamine content by HPLC provided evidence for altered endogenous serotonin neurotransmission in Del mice while there was no effect of genotype on any other monoamine. Moreover, we found that Del mice were highly sensitive to the 5‐HT2A antagonists M100907, which at a dose of 0.1 mg/kg normalized their level of active coping and restored the gradual shift to passive coping in the forced swim test. Supporting evidence for altered endogenous serotonin signaling was provided by observations of additional ligand effects including altered forebrain Fos expression. Taken together, these observations indicate notable changes in endogenous serotonin signaling in 16p11.2 deletion mice and support the therapeutic utility of 5‐HT2A receptor antagonists. Abstract : In humans a chromosomal hemideletion of the 16p11.2 region results in variable neurodevelopmental deficits including developmental delay, intellectual disability, and features of autism spectrum disorder (ASD). Mice modeling this human chromosomal hemideletion of the 16p11.2 region show robust perseverative active coping in response to acute stress (swim). This phenotype is completely normalized by a 5‐HT2A‐receptor antagonist. These results indicate a strong potential for the therapeutic utility of 5‐HT2A antagonists and also illustrate the utility of studying autism‐relevant mouse models in the context of stress.